2019
DOI: 10.1155/2019/8702324
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water Pressure on the Mechanical Properties of Concrete after Freeze-Thaw Attack under Dynamic Triaxial Compression State

Abstract: This study aims at determining the effect of water pressure on the mechanical properties of concrete subjected to freeze-thaw (F-T) attack under the dynamic triaxial compression state. Two specimens were used: (1) a 100 mm × 100 mm × 400 mm prism for testing the loss of mass and relative dynamic modulus of elasticity (RDME) after F-T cycles and (2) cylinders with a diameter of 100 mm and a height of 200 mm for testing the dynamic mechanical properties of concrete. Strain rates ranged from 10−5·s−1 to 10−3·s−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 48 publications
(65 reference statements)
0
7
0
1
Order By: Relevance
“…В частности, они могут быть востребованы при решении задач определения «оптимальных» параметров внутренней структуры бетонов, функционирующих в условиях влагонасыщения или в водной среде. Другим перспективным приложением, которое заслуживает отдельного упоминания, является оценка механического влияния воды на деградацию поверхностных слоев и износ поверхностных слоев бетонных элементов конструкций в крупных водоемах северных широт, в том числе в условиях арктического климата [12]. Такие опорные бетонные элементы находятся в условиях длительного контактного нагружения протяженными (десятки километров) ледовыми плитами толщиной до 1-2 м. При динамических подвижках ледовых массивов со скоростями до нескольких метров в секунду (например, при «льдотрясениях») локальные давления в пятнах контакта могут кратковременно достигать десятков мегапаскалей и даже превышать величину прочности бетона на одноосное сжатие.…”
Section: Introductionunclassified
“…В частности, они могут быть востребованы при решении задач определения «оптимальных» параметров внутренней структуры бетонов, функционирующих в условиях влагонасыщения или в водной среде. Другим перспективным приложением, которое заслуживает отдельного упоминания, является оценка механического влияния воды на деградацию поверхностных слоев и износ поверхностных слоев бетонных элементов конструкций в крупных водоемах северных широт, в том числе в условиях арктического климата [12]. Такие опорные бетонные элементы находятся в условиях длительного контактного нагружения протяженными (десятки километров) ледовыми плитами толщиной до 1-2 м. При динамических подвижках ледовых массивов со скоростями до нескольких метров в секунду (например, при «льдотрясениях») локальные давления в пятнах контакта могут кратковременно достигать десятков мегапаскалей и даже превышать величину прочности бетона на одноосное сжатие.…”
Section: Introductionunclassified
“…At the same time, knowledge of the local (mesoscopic) characteristics of concrete is of most importance in many topical practical problems. Examples of such problems are local contact loading of underwater parts of large concrete structures, including the collision of a ship with a concrete berth or dynamic contact load by ice plates during “icequakes” (analog of earthquakes in ice covers of large northern lakes or seas) [ 38 , 39 , 87 ]. Underestimation of local dynamic strength can have the far-reaching consequence of reducing the operational life of the entire concrete structure.…”
Section: Resultsmentioning
confidence: 99%
“…F I G U R E 2 2 SEM image of concrete after freezing-thawing cycle and triaxial compression (magnification 1000 times): (a)-(c) strain rate is 1 Â 10 À4 ; (d) 100 cycles with a strain rate of 1 Â 10 À3 . 38 At present, there is little research on the performance of concrete under a water pressure environment. However, with the continuous emergence of hydraulic concrete engineering, it is necessary to master the performance of concrete under a water pressure environment.…”
Section: Freezing and Thawing Cyclementioning
confidence: 99%
“…Researchers 36,37 paid attention to the permeability of ions under water pressure and found that high water pressure significantly increased the penetration depth of ions, resulting in different corrosion rates at different water pressures. Considering freeze–thaw damage of concrete caused by positive temperature in summer and negative temperature in winter, Wang et al 38 conducted dynamic triaxial compression tests on concrete after freeze–thaw cycles under different water pressures to observe microstructure changes and macro performance.…”
Section: Introductionmentioning
confidence: 99%